Praktikalitas Bahan Ajar Geometri Berbasis Modifikasi Model Project Based Learning (PjBL) “Kapal Nabi Nuh” untuk Mengembangkan Kemampuan Berpikir Kreatif Mahasiswa - Nasution, Eline Yanty Putri; Yulia, Putri (ARITHMETIC: Academic Journal of Math, 2024)
The available geometry teaching module at IAIN Kerinci still do not adequately accommodate students to discover material through scientific project tasks, and they are not yet integrated with Islamic values. The purpose of this research is to examine the practicality of geometry teaching materials based on modified Project Based Learning (PjBL) "Kapal Nabi Nuh." This type of research is Research and Development (R&D) using the 4-D model (Define, Design, Develop, Disseminate). The subjects of this research are 15 students of Class 2A in the Department of Mathematics Teaching at IAIN Kerinci. The instrument used in this research is a practicality questionnaire sheet assessed by the geometry course lecturer and students. The results of this research are geometry teaching module based on modified Project Based Learning "Kapal Nabi Nuh" declared practical, with a practicality response rate from lecturers obtained at 76.9% and from students obtained at 82.6%.